2014
DOI: 10.2147/vhrm.s64286
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac angiosarcoma: utility of [18F]fluorodeoxyglucose positron emission tomography–computed tomography in evaluation of residue, metastases, and treatment response

Abstract: Cardiac angiosarcomas are a rare form of malignancy. The majority of cases arise from the right atrium as mural masses. These tumors have extremely aggressive behavior, with early clinical symptoms that vary depending on location, size, and extent of the tumor. Most of these patients have a very short survival time. Surgical therapy is considered the best choice of therapy approach in cardiac angiosarcoma patients with nonmetastatic disease, even though the disease is rarely cured. Advanced diagnostic techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In this study, we showed that SUV max of angiosarcoma primary lesions could potentially predict prognosis. There are several case reports on the use of PET/CT in angiosarcoma, but to the best of our knowledge, this is the first reported case series in which PET/CT use for CAS was systematically reviewed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we showed that SUV max of angiosarcoma primary lesions could potentially predict prognosis. There are several case reports on the use of PET/CT in angiosarcoma, but to the best of our knowledge, this is the first reported case series in which PET/CT use for CAS was systematically reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed that SUV max of angiosarcoma primary lesions could potentially predict prognosis. There are several case reports on the use of PET/CT in angiosarcoma, [11][12][13][14] but to the best of our knowledge, this is the first reported case series in which PET/CT use for CAS was systematically reviewed. Positron emission tomography/CT is a combined imaging modality in which PET scans generate functional information while CT scans generate morphological information.…”
Section: Discussionmentioning
confidence: 99%
“…Scattered case reports in literature describe how integrated PET/CT with FDG imaging can incidentally show cardiac neoplasia, particularly metastatic involvement, 11 17 or may be used in case of suspected aggressive cardiac malignancy to strengthen the diagnosis and detect possible occult distant disease. 18 26 …”
Section: F-fluorodeoxyglucose Positron Emission Tomogramentioning
confidence: 99%
“…10 18 F-fluorodeoxyglucose positron emission tomography/computed tomography Scattered case reports in literature describe how integrated PET/CT with FDG imaging can incidentally show cardiac neoplasia, particularly metastatic involvement, [11][12][13][14][15][16][17] or may be used in case of suspected aggressive cardiac malignancy to strengthen the diagnosis and detect possible occult distant disease. [18][19][20][21][22][23][24][25][26] However, unlike many other solid tumors, FDG PET does not have an established role in the routine evaluation of cardiac tumors, which is probably due both to their low frequency and to the physiologically high uptake of FDG in the myocardium, although with interindividual and intraindividual variability. 27 In the normal myocardium, metabolism is primarily oxidative and uses various substrates, including glucose, free fatty acids and lactate.…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…Tumour response to therapy can also be evaluated using the metabolic activity of lesions with PET. PET and MRI are also useful in distinguishing scar tissue from recurrence [ 20 ].…”
Section: Cardiac Massesmentioning
confidence: 99%